An Appraisal of Multibeam Echosounder Calibration - Mahmud, Mohd. Razali; M. D. E. K., Gunathilaka; Tang, Kelvin Kang Wee (2007)
One of the most impressive hydrographic technique developed over the past few decade is multibeam sonar systems. Sounding data from these systems is a result of processing information from several data sources. Among them, positional data from Global Positioning System (GPS), vessels heading and attitude data from gyrocompass and motion sensor systems, vertical reference data from tide gauge and sound speed data, in addition to the multibeam data itself. There must be a good coordination between these systems in order to obtain reliable data. To determine this, a proper and thorough field calibration procedure has to be carried out on the system as a whole. This process begins with measurement of static offsets between each sensor system with reference to a fixed point on the vessel. Preferably, the point of centre of gravity (COG). Then the patch test is carried out to determine the mounting offsets and GPS latency and lastly a performance test to verify whether the data meet the accuracy requirements for the survey. This is achieved through a comparison of data with a reference surface. This paper discusses the theoretical aspects, steps involved and results of the calibration procedures for multibeam sonars, using RESON SeaBat 8124 multibeam system. Finally, a summary of multibeam sonar calibration criteria is also presented showing the methodology involve which include when to perform each test and applying corrections.